Internal Branding in der Zeitarbeit: Ist markenkonformes Verhalten und die Identifikation mit der Unternehmenskultur des Einsatzunternehmens bei Zeitarbeitsverhältnissen realisierbar? - Nick Brandolini; Florian Botzenhardt; Jens U. Pätzmann (Markenbrand, 2014)
– The following article takes a close view onto the relationship between internal branding, corporate culture and temporary employment. Starting from the question whether brand-oriented behaviour and identification with the corporate culture is achievable under the special circumstances of labour leasing, the authors develop the Internal Branding Corporate Culture Model in Labour Leasing (IBUK-Modell der Zeitarbeit). It is based on existing models for internal brand management and corporate culture and incorporates both insights from expert interviews and literature review while being tailored to the special needs of labour leasing employment conditions. The model shows that brand-oriented behaviour and identification with corporate culture can be achieved while managing temporary workers via specific processes, components and measures. Finally recommended courses of actions for marketers, human resource specialists and managers are given and the possibility to use labour leasing as a recruitment method is being explained.
Keywords: 650